PENGARUH KOMUNIKASI, MOTIVASI DAN LINGKUNGAN, KERJA FISIK TERHADAP KEPUASAN KERJA PEGAWAI SEKRETARIAT DAERAH KOTA DENPASAR - Kresna Wirawan, I Dewa Gede; Sudharma, I Nyoman (E-Jurnal Manajemen, 2015)
Job satisfaction  problems that occur in Sekretariat Daerah Kota Denpasar is the relationship between leaders and subordinates who are less well established where leaders failed to give motivation and attention to his subordinates. Thetpurpose oftthis studyuwas toodetermine the effectyof communication, motivation andyphysicaliwork environment on . employe satisfaction. This research wast conductedt the Sekretariat Daerah Kota Denpasar. The number of samples used 80 people with sampling methods saturated. Interviews and question were use for data collection. Multiplet linear regres in technique rusedt in this study. Based on the analysis communicatin, motivation mand physical environment simultaneously and partially positive and significant impact on employee job satisfaction. Limitations of this study where researchers only use three variables to measure job satisfaction. Further research should further refine this study by adding other variables related to job satisfaction.
Keywords: communication, motivation, physical work environment, job satisfaction.